Angiographic and risk factor characteristics of subjects with early onset ischaemic heart disease. Issue 3 (September 1981) - Nitter-Hauge, S; Erikssen, J; Thaulow, E; Vatne, K
Abstract : Sixty-six consecutive patients less than 40 years of age with angiographically documented coronary artery disease and coronary heart disease took part in a study aimed at (1) identifying the presence of factors which might explain the premature onset of ischaemic heart disease, and (2) assessing the distribution and severity of the coronary artery lesions. For comparisons we have used a study of risk factors in 1832 men defined as "normals" according to a recent comprehensive examination. The findings show that the typical early onset coronary heart disease case is an overweight, heavily smoking male "blue collar" worker, with high serum levels, a marginally raised blood pressure, and a high prevalence of coronary heart disease among first degree relatives. Coronary angiography showed a preponderance of one vessel disease. In particular, left anterior descending artery lesions were common, which might have contributed to the early manifestation of disease.